J Diabetes Metab 2019
DOI: 10.35248/2155-6156.19.10.819
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Multicentre, Single Arm Clinical Study to Evaluate the Effect of Saroglitazar on Non High-Density Lipoprotein Cholesterol in Patients with Diabetic Dyslipidemia Inadequately Controlled with Diet, Exercise, and Statin-The GLIDDER Study

Abstract: Objective: Diabetic dyslipidemia is highly atherogenic as it is associated with high triglyceride (TG), high small dense low-density lipoprotein (sd-LDL) particles and low High-Density Lipoprotein Cholesterol (HDL-C). Saroglitazar, a dual peroxisome proliferator activated receptor agonist (predominant PPAR-α agonist and modest PPAR-γ agonist), is approved in India for the management of diabetic dyslipidemia. The GLIDDER study was done to evaluate the effects of Saroglitazar 4 mg on non HDL-C as the primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 24 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…Kaul et al [21] was the first study to examine the effects of Saroglitazar on non-HDL-C as the primary endpoint and sd-LDL-C as a secondary endpoint in 104 patients with diabetic dyslipidemia. The authors observed significant decrease in non-HDL-C (baseline: 142.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Kaul et al [21] was the first study to examine the effects of Saroglitazar on non-HDL-C as the primary endpoint and sd-LDL-C as a secondary endpoint in 104 patients with diabetic dyslipidemia. The authors observed significant decrease in non-HDL-C (baseline: 142.…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al [30] conducted a 58 weeks observation study of Saroglitazar in 158 patients with diabetic dyslipidemia (baseline TG ≥ 150 mg/dL). The authors found significant [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]: Group 1 (12 weeks): Shetty et al [13], Thacker et al [14], Joshi et al [15], Bhattacharyya et al [16]; Group 2 (24 weeks): Saboo et al [17], Joshi et al [18], Chhaya et al [19], Mohit et al [20], Kaul et al [21], Goyal et al [22]; Group 3 (27 weeks): Chatterjee et al [23]; Group 4 (36 weeks): Joshi et al [24]; Group 5 (40 weeks): Chatterjee et al [25]; Group 6 (52 weeks): Joshi et al [26], Aneja et al [27], Maheshwari et al [28], Chatterjee et al [29]; Group 7 (58 weeks): Chatterjee et al [30]. Mean non-HDL-C calculation: data not available for Thacker et al [14], Saboo et al [17], Joshi et al [18], Chhaya et al [19], Mohit et al [20], Goyal et al [22] reduction in TG (baseline: 319.9 ± 178.8 mg/dL to week-58: 174.0 ± 113.6 mg/dL...…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations